2022
DOI: 10.1177/15353702221108915
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of medicinal plant-derived products against SARS-CoV-2

Abstract: This review presents information from several studies that have demonstrated the antiviral activity of extracts ( Andrographis paniculata, Artemisia annua, Artemisia afra, Cannabis sativa, Curcuma longa, Echinacea purpurea, Olea europaea, Piper nigrum, and Punica granatum) and phytocompounds derived from medicinal plants (artemisinins, glycyrrhizin, and phenolic compounds) against SARS-CoV-2. A brief background of the plant products studied, the methodology used to evaluate the antiviral activity, the main fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 99 publications
0
11
0
Order By: Relevance
“…They could also interact either directly or indirectly with the Cys/His dyad of the main protease to inhibit viral replication. In this way, polyphenols could interfere with viral pathogenesis in various stages [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…They could also interact either directly or indirectly with the Cys/His dyad of the main protease to inhibit viral replication. In this way, polyphenols could interfere with viral pathogenesis in various stages [ 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides HT, other phenolic compounds have shown to exhibit antibacterial effects against several strains of bacteria responsible for intestinal and respiratory infections in vitro [ 66 , 69 , 70 , 71 ], with promising results for applications as preservatives in food industry [ 23 , 62 , 72 , 73 ], in particular reducing the growth of Helicobacter pylori, which is associated with peptic ulcers and gastric cancer [ 66 ]. OLE polyphenols have also revealed antiviral and antiprotozoal activities [ 17 , 61 , 74 , 75 , 76 ]. The present study tested the inhibitory capacity of the OLEs from all three selected cultivars against Gram(+) strains— S. aureus (ATCC 25923) , S. epidermidis (NCTC 11047), B. cereus (ATCC 14579)—and Gram(−) strains— E. coli (NCTC 9001), Salmonella Enteritidis (ATCC 13076), and P. aeruginosa (ATCC 10145).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, purified HT from olive and a patented HT, HIDROX ® , have been shown to inactivate SARS-CoV-2. They altered the spike protein, significantly impacting the viral genome [ 165 ]. A similar effect has been reported in molecular docking by Geromichalou et al He demonstrated the EVOO compound’s potential to bind to inhibit the SARS-CoV-2 spike protein via targeting angiotensin-converting enzyme 2 (ACE2) and the receptor-binding domain (RBD) [ 166 ].…”
Section: Olive Bioactive Molecules In Infectious Respiratory Diseasesmentioning
confidence: 99%